Analysis of Teaching Practices During the COVID-19 Pandemic: Teachers’ Goals and Activities in Virtual Classrooms - Echeverría, María-Puy Pérez; Pozo, Juan-Ignacio; Cabellos, Beatriz (Frontiers in Psychology, 2022)
To research teachers’ priorities during the COVID-19 lockdown, we asked Spanish Primary and Secondary teachers to describe an activity they had done with their students. We obtained 272 activities that we analyzed according to the proposed goals, the types of learning worked (verbal, procedural, and attitudinal), and the kind of teaching promoted (content or student-centered). Results showed that most teachers proposed content-centered activities, oriented above all to verbal learning. There were clear differences between the proposed goals, partly student-centered, and what was really taught, essentially content-centered. We obtained two teaching profiles, one reproductive and the other constructive.